Fully implantable, multi‐channel microstimulator with tracking supply ribbon, multi‐output charge pump and energy recovery - Amin Rashidi; Niloofar Yazdani; Amir M. Sodagar (IET Circuits, Devices and Systems)
Abstract A novel energy‐efficient approach dedicated to high‐density implantable stimulators such as visual prostheses is presented. Energy efficiency of the approach proposed in this work is achieved through two ideas: the ‘tracking supply ribbon’ technique and ‘reverse charge pumping’. The proposed approach is implemented, in the multi‐channel case, in such a way that power efficiency of each stimulation channel is enhanced according to its specific voltage/current condition and independently from other channels. For this purpose, a multi‐channel power‐efficient charge pump circuit with small integrated capacitors is proposed. Based on the proposed approach, a fully integrated 16‐channel stimulation backend for a visual prosthesis was designed and simulated in the transistor level in a standard 0.18‐μm triple‐well CMOS technology, occupying 1.41 mm2 of silicon area. According to post‐layout simulation results, power savings of up to 74% for a single channel and 81.5% for multiple channels are achieved compared to the conventional output stage with a constant supply voltage. Designed for the proposed stimulation backend, the charge pump generates output voltages of 3.48 V, −1.69 V, −3.38 V, and −5.05 V out of a 1.8 V input voltage and exhibits average power efficiency of 92.8% and 86.8% for one‐ and three‐stage circuits, respectively, all in the case of a 100 μA current load. All the aforementioned results are based on post‐layout simulation. Moreover, a proof‐of‐concept prototype was developed using off‐the‐shelf components in order to demonstrate the operation of the proposed tracking supply ribbon idea.